2013
DOI: 10.1186/1479-5876-11-235
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose azathioprine is effective in maintaining remission among Chinese patients with Crohn’s disease

Abstract: BackgroundAzathiopurine (AZA) is efficacious for maintenance remission of Crohn’s disease (CD) at the standard dose of 2.0-2.5 mg/kg for Caucasian. It has been reported that the lower dose (1.0-2.0 mg/kg) in some Asian countries was as effective as the standard dose. In the present study we analyzed the efficacy of <1.0 mg/kg AZA in maintaining remission for Chinese patients.MethodsThe clinical data of all CD patients were reviewed from 1993 to December 2012. The patients who initiated AZA treatment and were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…retrospectively studied 178 CD patients and found that AZA at 1.24 ± 0.16 mg/kg per day might be an appropriate dose for Chinese CD patients. Wu et al . enrolled 77 CD patients and suggested that AZA <1.0 mg/kg was as effective as that at 1.0–2.0 mg/kg in maintaining remission.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…retrospectively studied 178 CD patients and found that AZA at 1.24 ± 0.16 mg/kg per day might be an appropriate dose for Chinese CD patients. Wu et al . enrolled 77 CD patients and suggested that AZA <1.0 mg/kg was as effective as that at 1.0–2.0 mg/kg in maintaining remission.…”
Section: Discussionsupporting
confidence: 82%
“…Patients who stopped AZA treatment for fear of adverse effects, no response (or thought to be non‐responded), recurrence or surgery were not included in the studies. Wu et al . found that the doses in patients who did not achieve remission were significantly higher than those in patients who did, which means that bias existing in these retrospective studies cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations